OTENTISITAS DALAM PENGELOLAAN ARSIP ELEKTRONIK: STUDI KASUS DI BADAN PERPUSTAKAAN DAN ARSIP DAERAH (BPAD) PEMERINTAH PROVINSI DKI JAKARTA: Array - Nina Mayesti; Tyan Hanriarseto (Arsip Nasional Republik Indonesia, 2013)
This article discusses authenticity in electronic record management at Badan Perpustakaan and Arsip Daerah Pemprov DKI Jakarta. The focus is on how to protect and maintain the authenticity of electronic record. The purpose is to find out the procedures and to identify BPAD efforts for maintaining authenticity in managing electronic record. This research applied qualitative approach with a case study method. Depth interview, observation and study documents were techniques used as a data collecting method. The result was that BPAD efforts to maintain authenticity of electronic record were still low. However, it didn’t mean that BPAD made no attempt to maintain the authenticity of electronic records. There have been some efforts, though; it didn’t have a detailed procedure of what should be done.